Indonesia Responsibility of Transboundary Haze Pollution by Forest Fires in Perspective of International Environmental Law - Noor, Dimitri Anggrea (GoAcademica Research & Publishing, 2023)
At a meeting of environment ministers ASEAN Sub Regional Ministerial Steering Committee on Transboundary Haze Pollution (MSC), Malaysia urges Indonesia to resolve the haze problem by forest fires causing health problems to society and a number of harmful interference Malaysia and Singapore. This leads to the creation of national and international instruments to prevent and control transboundary haze pollution by forest fires. This writing uses a normative legal research method. It also uses cases that refer to cases of forest fires which have occurred as well as the statutory approach that analyzes national laws and international instruments. This writing discusses two main issues, namely: Indonesia responsibility by national law and international environmental law on transboundary pollution by forest fires and Indonesia law action related responsibility on transboundary pollution by forest fires. As for the conclusions that can be drawn are as follows: 1) That Indonesia's responsibility can be carried is increase forest protection efforts, apply sanctions in assertive, give some information and education about dangerous air pollution, responsibility in morals, oversee climate change, and more selective to give permission in forest exploitation. 2) Indonesia legal action related to responsibility can be seen by policy and Indonesia steps and enforcement in resolving forest fires. One of Indonesia's legal actions to resolve forest fires is the issuance of a presidential decree or the Presidential Instructions of the Republic of Indonesia number 11 years 2015 concerning Improvement of Fire Control. This instruction sets government officials to resolve and teamwork and increase law enforcement and assertive sanctions for forest fires activity